TB Peritonitis Mistaken for Ovarian Carcinomatosis Based on an Elevated CA-125 - Joseph D. Boss; Christopher T. Shah; Oladoyin Oluwole; John N. Sheagren (Case Reports in Medicine)
Background. In the United States, tuberculosis (TB) is of relatively low prevalence and most newly diagnosed patients are born outside of the United States. In addition, a large percentage (20.6%) of TB cases initially present with extrapulmonary manifestations (CDC, 2010). Cases of TB peritonitis are a diagnostic challenge in women due to the nonspecific clinical features overlapping with signs of ovarian cancer. (Kosseifi et al., 2009; Rashed et al., 2007; and Xi et al., 2010). We present a 27 year-old woman thought to have ovarian carcinomatosis based on elevated levels of CA-125 who was ultimately diagnosed with TB salpingitis, endometritis, and peritonitis. Methods. This brief report is a retrospective case report. Results. This case outlines the unfortunate consequences of the misdiagnosis of what probably was an antibiotic responsive illness, resulting in an unnecessarily aggressive surgical procedure. The delay in the diagnosis of tuberculous pertitonitis resulted in an unnecessary radical resection of the patient’s reproductive organs. Conclusions. Patients with TB peritonitis present with non-specific signs that may be misdiagnoses as ovarian cancer. In differentiating between ovarian carcinomatosis and peritoneal TB, it is vital to consider country of origin, age, CA-125, ascitic fluid analysis, and the use of intra-operative frozen sections.